2016
DOI: 10.1093/jamia/ocw125
|View full text |Cite
|
Sign up to set email alerts
|

Computerized prescriber order entry–related patient safety reports: analysis of 2522 medication errors

Abstract: Errors related to CPOE commonly involved transmission errors, erroneous dosing, and duplicate orders. More standardized safety reporting using a common taxonomy could help health care systems and vendors learn and implement prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 19 publications
2
53
0
1
Order By: Relevance
“…It is important to learn more about the most common types of errors that take place in the prescribing phase, as they may differ from those in other phases of the medication use process. In one study, our team previously found that the most common types of errors associated with CPOE found in incident reports were due to errors in the transmission of prescriptions, erroneous dosing and duplicate orders 3. Therefore, two of the three most common errors in the prescribing phase (wrong patient, wrong drug) in our study may not have been noted as most common through review of incident reports.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It is important to learn more about the most common types of errors that take place in the prescribing phase, as they may differ from those in other phases of the medication use process. In one study, our team previously found that the most common types of errors associated with CPOE found in incident reports were due to errors in the transmission of prescriptions, erroneous dosing and duplicate orders 3. Therefore, two of the three most common errors in the prescribing phase (wrong patient, wrong drug) in our study may not have been noted as most common through review of incident reports.…”
Section: Discussionmentioning
confidence: 73%
“…When the free text responses from the clinicians who replied to the email query were reviewed by two pharmacists and categorised using a previously validated taxonomy,3 the top reasons explicitly stated in their emails for ‘what happened in CPOE’ included: medication ordered for wrong patient (27.8%, n=60); wrong drug ordered (18.5%, n=40); and duplicate order placed (14.4%, n=31) (table 2). Prescriber responses also included comments that highlighted confusing aspects of the CPOE system and look-alike/sound-alike drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heringa et al [9] focused on decreasing the alert rates by clustering relevant drug interaction alerts, while Lilih et al [10] proposed a method for improving the effectiveness of drug safety alerts to increase adherence to guidelines for gastrointestinal prophylaxis. In addition, Amato et al [11] analyzed a large number of CPOE-related patient safety reports that occurred in the medication ordering phase from six sites participating to a project examining CPOE safety. In the domain of drug safety, Botsis et al [12] presented a decision support environment for medical product safety surveillance, which has been developed by the Food and Drug administration (FDA).…”
Section: Contributions From the 2016 Literature On Clinical Decision mentioning
confidence: 99%
“…While not a pediatrician, as a primary care physician and patient safety researcher I have spent considerable time both submitting and reviewing safety reports [5,6]. At one point, I had filed more error and adverse drug reactions reports than all the other physicians at my public hospital in Chicago combined, making me either the institution’s most dangerous prescriber or its most diligent reporter [7].…”
mentioning
confidence: 99%